BNT162b2 Vaccination Elicits Strong Serological Immune Responses Against SARS-CoV-2 Including Variants of Concern in Elderly Convalescents - Jahrsdörfer, Bernd; Fabricius, Dorit; Scholz, Judith; Ludwig, Carolin; Grempels, Aline; Lotfi, Ramin; Körper, Sixten; Adler, Guido; Schrezenmeier, Hubert (Frontiers in Immunology, 2021)
Elderly residents of long-term care facilities (LTCFs) have long been underrepresented in studies on vaccine efficacy, particularly in light of currently emerging variants of concern (VOCs). In this prospective observational cohort study, we analyzed serological immune responses in 190 individuals before, 3 weeks after 1st and 3 weeks after 2nd vaccination with BNT162b2. Unvaccinated COVID-19-convalescent subjects served as reference. End points comprised serum anti-spike IgG and IgA titers as well as neutralization capacities against unmutated and mutated SARS-CoV-2 receptor binding domains including B.1.1.7, B.1.351 and P.1. We found that antibody titers and neutralization capacities up to 3 weeks after 2nd vaccination with BNT162b2 were significantly higher in COVID-19-convalescent as compared to COVID-19-naive vaccinees. Moreover, pre-vaccination anti-NCP IgG titers, but not age or gender, had a high impact on the strength and kinetics of post-vaccination neutralization capacity development. Most importantly, BNT162b2-induced neutralization capacity was cross-reactive with VOCs. In contrast to unvaccinated convalescents, vaccinated convalescent individuals of all ages acquired strong neutralizing capacities against current VOCs. The present study suggests that COVID-19-convalescent individuals with a broad age range between 18 and 98 years benefit from BNT162b2 vaccination by developing strong and broad neutralizing immune responses against SARS-CoV-2 including current VOCs.